Isolated abnormal diffusing capacity for carbon monoxide (iso↓DLco) is associated with increased respiratory symptom burden in people with HIV infection. - Katerina L Byanova; Jessica Fitzpatrick; Amanda K Jan; Maggie McGing; Marlena Hartman-Filson; Carly K Farr; Michelle Zhang; Kendall Gardner; Jake Branchini; Robert Kerruish; Sharvari Bhide; Aryana Bates; et al. (PLoS ONE)
Objectives An isolated reduction in the diffusing capacity for carbon monoxide (DLco; iso↓DLco) is one of the most common pulmonary function test (PFT) abnormalities in people living with HIV (PWH), but its clinical implications are incompletely understood. In this study, we explored whether iso↓DLco in PWH is associated with a greater respiratory symptom burden. Study design Cross-sectional analysis. Methods We used ATS/ERS compliant PFTs from PWH with normal spirometry (post-bronchodilator FEV1/FVC ≥0.7; FEV1, FVC ≥80% predicted) from the I AM OLD cohort in San Francisco, CA and Seattle, WA, grouped by DLco categorized as normal (DLco ≥lower limit of normal, LLN), mild iso↓DLco (LLN >DLco >60% predicted), and moderate-severe iso↓DLco (DLco ≤60% predicted). We performed multivariable analyses to test for associations between DLco and validated symptom-severity and quality of life questionnaires, including the modified Medical Research Council dyspnea scale (mMRC), the COPD Assessment Test (CAT), and St. George's Respiratory Questionnaire (SGRQ), as well as between DLco and individual CAT symptoms. Results Mild iso↓DLco was associated only with a significantly higher SGRQ score. Moderate-severe iso↓DLco was associated with significantly higher odds of mMRC ≥2 and significantly higher CAT and SGRQ scores. PWH with moderate-severe iso↓DLco had increased odds of breathlessness, decreased activity, lower confidence leaving home, and less energy. Conclusions Iso↓DLco is associated with worse respiratory symptom scores, and this association becomes stronger with worsening DLco, suggesting that impaired gas exchange alone has a significant negative impact on the quality of life in PWH. Additional studies are ongoing to understand the etiology of this finding and design appropriate interventions.